Analyzing the Movie "Hidden Figures" (2016): A Comprehensive Examination of Race and Gender Inequality - Karina Rizky Amanda; Nisa Rahmayanti Purwanto; Vianita Nur Fitri Putri Ramadhani; Nabila Putri Siswandini; Haniya Meisya Angraini (The Innovation of Social Studies Journal, 2024)
Hidden Figures is a movie based on a true story that told a story about the challenges of being black race women due to racial and gender discrimination in the society at that time. This study aims to examine how Hidden Figures portrays black feminism of the injustice against the black race and the complexities of women in gender inequality, particularly within the historical context that highlights the experiences of women. This research is based on descriptive analysis methods. Descriptive analysis is used to reveal the representation of gender inequality, racial injustice, and black women feminism in Hidden Figures by examining the characters' interactions, dialogue, and narrative choices. The analysis revealed the injustice against the black race in society experienced by the characters in the movie. Furthermore, this study showed gender inequality that happened in the movie Hidden Figures. It can be concluded that Hidden Figures portrays issues such as racial and gender barriers, especially to black women in workspace. In addition, the movie Hidden Figures also added a conclusion to this study, in which complexity of women in gender inequality is a concerning issue in the film.